Intellectual Property Challenges in the Digital Marketplace: An Analytical Exploration of Trademark Rights in Contemporary E-Commerce Jurisprudence - Merebashvili, Tornike (Eximia, 2024)
Trademark law is one of the IP laws that has been imposed to protect the rights of trademark holders against infringement. This law has always been enforced to ensure that consumer rights are protected and that the trademark holders are protected against infringement. However, the emergence of the internet and the widespread use of the internet have created new legal problems as it is no longer possible to enforce trademark rights due to the nature of cyberspace. This paper evaluates the legal challenges experienced in enforcing trademark rights in the digital era. The analysis con-ducted has established that the use of e-commerce has led to the emergence of new challenges that can no longer be solved by the laws in jurisdictions. Since the internet cannot be categorized into a particular territory, the jurisdiction laws can no longer apply due to the law differences in countries. There is a need for a uniform international framework that will help in enforcing trademark rights across the borders of different countries.